2011
DOI: 10.1002/chem.201003713
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxy‐ and Aminophenyl Radicals from Arenediazonium Salts

Abstract: A buried polar bilayer interface composed of interdigitated peptide ends and a high density of CF3COO− counterions passifying lysine amines are identified in nanotubes obtained by self‐assembly of short peptides. The structure reveals distinct characteristics that differentiate peptide bilayers and lipid bilayers that can now be exploited for the construction of lipid‐like nanomaterials with protein functionality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(20 citation statements)
references
References 79 publications
2
17
0
Order By: Relevance
“…For certain substrates, the Ti III -mediated arylation of furans with diazonium salts might have potential as a useful alternative. [14] It has been reported, though, that Meerwein-type arylation reactions cannot be applied to the synthesis of 2,5-diarylfurans such as 6 or 9, [7] which have instead been synthesized from symmetrical 2,5-distannylfurans [15] in double Stille couplings. The disadvantages of this method include potential contamination of the products with organostannane residues, as well as selectivity issues arising when the method is adopted for the synthesis of unsymmetrical 2,5-diarylfurans.…”
Section: Introductionmentioning
confidence: 99%
“…For certain substrates, the Ti III -mediated arylation of furans with diazonium salts might have potential as a useful alternative. [14] It has been reported, though, that Meerwein-type arylation reactions cannot be applied to the synthesis of 2,5-diarylfurans such as 6 or 9, [7] which have instead been synthesized from symmetrical 2,5-distannylfurans [15] in double Stille couplings. The disadvantages of this method include potential contamination of the products with organostannane residues, as well as selectivity issues arising when the method is adopted for the synthesis of unsymmetrical 2,5-diarylfurans.…”
Section: Introductionmentioning
confidence: 99%
“…This scale, based on the electrophilicity index as introduced by Parr et al [2] (for a recent review see Chattaraj et al [3]) and defined as the electronic chemical potential squared over two times the chemical hardness, has proven its value since assisting in classifying radical systems [4][5][6][7][8][9][10], explaining reaction behavior and introducing other chemical concepts like radical stability [11][12][13][14]. The question arises, though, as to whether the order of this gas-phase electrophilicity scale still holds for radicals in solution.…”
Section: Introductionmentioning
confidence: 99%
“…117 This study on the previously rarely examined 2-and 4-hydroxyphenyldiazonium ions demonstrated that the related 2-and 4-hydroxyphenyl radicals also show exceptional behaviors in biphasic reaction mixtures. Apparently as a result of their high polarity, these radicals react preferentially in the aqueous phase, so that selective arylation of protonated furfurylamine can be achieved in the presence of an equal amount of 2-methylfuran dissolved in cyclohexane.…”
Section: Scheme 31 Synthesis Of Biaryl 105 From 2-hydroxyphenyldiazonmentioning
confidence: 94%
“…117 An analogous experiment with the related 4-hydroxyphenyldiazonium salt provided the corresponding biaryl in 48% yield.…”
Section: Account Syn Lettmentioning
confidence: 97%
See 1 more Smart Citation